Burden of varicella in Latin America and the Caribbean: findings from a systematic literature review - Luiza Helena Falleiros Arlant; Maria Catalina Pirez Garcia; Maria L. Avila Aguero; Miguel Cashat; Cintia Irene Parellada; Lara J. Wolfson (BMC, 2019)
Abstract Background Varicella is typically mild and self-limiting, but can be associated with complications and even death. The limited data available on varicella in Latin America and the Caribbean (LAC) indicate substantial burden in countries where varicella vaccine is not part of publicly funded childhood national immunization programs. Methods A systematic literature review of published studies was complemented by "gray" literature on varicella incidence, complications, mortality, and economic consequences, in the absence and presence of universal varicella vaccination (UVV) in LAC. Results Seroprevalence data indicate that varicella is usually a disease of childhood in LAC. Varicella incidence rates, while unreliable in the absence of mandatory reporting, show a trend to increased incidence due to greater urbanization and population density. The introduction of UVV in national immunization programs has led to significant reductions in varicella incidence in these areas. Conclusions Varicella continues to pose a substantial healthcare burden in LAC. The future introduction of UVV in additional countries is predicted to provide substantial reductions in cases, with important economic benefits. For countries that have already implemented UVV, the challenge is to maintain high rates of coverage and, where relevant, consider inclusion of a second dose to reduce breakthrough cases. Given the significant proportion of the region now implementing UVV, a regional recommendation in order to prevent any potential for age-shifts in varicella infection might be considered.